Mitigating social isolation following the COVID-19 pandemic: remedy messages shared by older people - Low, Gail; von Humboldt, Sofia; Gutman, Gloria; Gao, Zhiwei; Allana, Hunaina; Naz, Anila; Wilson, Donna M.; Vastani, Muneerah (My University, 2024)
At the beginning of July 2022, when public health restrictions were lifted, we deployed a country-wide e-survey about how older people were managing now after COVID-19 pandemic-related anxiety. Our responder sample was stratified by age, sex, and education to approximate the Canadian population. E-survey responders were asked to share open-text messages about what contemporaries could do to live less socially isolated lives at this tenuous turning point following the pandemic as the COVID-19 virus still lingered. Contracting COVID-19 enhanced older Canadians’ risk for being hospitalized and/or mortality risk. Messages were shared by 1189 of our 1327 e-survey responders. Content analysis revealed the following four calls to action: (1) cultivating community; (2) making room for what is good; (3) not letting your guard down; and (4) voicing out challenges. Responders with no chronic illnesses were more likely to endorse making room for what is good. Those with no diploma, degree, or certificate least frequently instructed others to not let their guard down. While COVID-19 is no longer a major public health risk, a worrisome proportion of older people across the globe are still living socially isolated. We encourage health and social care practitioners and older people to share messages identified in this study with more isolated persons.
Keywords: COVID-19; remedy messages; older adults